Physical Activity among Nepalese Teachers; the Perspective of Role Modeling - Aryal, Bhagwan (Shiksha Shastra Saurabh, 2022)
Physical activity is any form of involvement in exercise or movement of the body that uses energy. Teachers also need an appropriate amount of physical activity because they are observed by their students in many ways, including their exercise behavior and fitness. Although an adult requires a minimum of 150 minutes (or at least 3 days) of additional physical activity in a week, this study shows that the sampled teachers were not in this mark. This cross-sectional survey of 344 teachers in 46 secondary schools in Bagmati Province of Nepal found the physical activity behavior among Nepalese teachers with the perspective of role modeling for health promotion. It has been argued that teachers who have average healthy behaviors and lifestyles with respect to physical activity neither make them healthier nor contribute to the creation of healthy role models in schools. The age and gender of the teacher were found to determine the degree of physical activity. More than two-thirds of her teachers were not reaching the recommended weekly physical activity level. More than two-fifths of the teachers did not receive training once a week. Physical activity among the teachers was recommended to present them as healthy role models.